Origins of diastereoselectivity in mannich additions to 4-substituted piperideines and studies toward enantioselective alternatives - SORTO, Jenny Esmeralda Padilla (2024)
A conventional and simple methodology for the synthesis of cyclic imines was harnessed to prepare three examples of 4-substituted-2,3,4,5-tetrahydropyridines. The prepared piperideines were employed as substrates in a tunable diastereoselective, and chromatography-free Mannich reaction to access structurally novel coumarin-containing N-heterocycles. The transformation was studied experimentally, and a theoretical study was also performed by DFT calculations employing the reaction between 4-methylpiperideine and 4-hydroxycoumarin as a model. Thus, trans-, or cis- configurational isomers were obtained in high purity by solely varying temperature and solvent. The study suggested a Curtin-Hammett behavior, and combined acid catalysis and solvent effect examinations revealed significant mechanistic information by using LSER modeling with Kamlet-Taft solvent polarity empirical scales. Thermodynamic parameters of activation were estimated by experimental data arising from Eyring-type plots. Also, 4-hydroxy-6-methyl-2-pyrone and 5,5-dimethyl-1,3-cyclohexanedione were explored as nucleophiles to explore the scope of the model reaction. Finally, new enantioselective alternatives were tested to obtain these adducts, from which a previously developed EKR step was improved to be proposed as a feasible alternative for their production as pure enantiomers. Other novel N-heterocycles derived from the 4-substituted piperideines such as cyclic enamides and enamines were successfully prepared and analyzed for the enrichment of the present study.